Low-Dose Slow Infusion Tissue Plasminogen Activator (tPA) in Treatment of Thrombotic Coronary Artery Occlusions: Case Series and Literature Review - Murat Akçay; Metin Çoksevim; Ufuk Yıldırım; Ömer Gedikli; Okan Gülel; Serkan Yüksel; Murat Meriç; Korhan Soylu; Özcan Yılmaz; Mahmut Şahin (Anatolian Journal of Cardiology, 2022)
Thrombotic coronary artery occlusions usually manifest as acute coronary syndrome with cardiogenic shock, acute pulmonary edema, cardiac arrest, fatal arrhythmias, or sudden cardiac death. Although it usually occurs based on atherosclerosis, it can also occur without atherosclerosis. There is no predictor of coronary artery thrombosis clinically and no consensus regarding the optimal treatment. In the current literature, treatment options include emergency coronary artery bypass grafting, entrapment of thrombus in vessel wall with stent implantation, intracoronary thrombolysis, glycoprotein IIb/IIIa inhibitors, anticoagulation with heparin, and thrombus aspiration as reperfusion strategies. Here, we reviewed a new treatment strategy based on the literature, and a case series with successful results in hemodynamically stable patients with low-dose slow infusion tissue plasminogen activator (tPA) for thrombotic coronary artery occlusions that allow coronary flow was reported. Prospective randomized studies and common consensus are needed on low-dose, slow-infusion tissue plasminogen activator treatment regimen and optimal treatment management for thrombotic coronary artery occlusions.